2017
DOI: 10.1002/2016jd026030
|View full text |Cite
|
Sign up to set email alerts
|

Regional and local new particle formation events observed in the Yangtze River Delta region, China

Abstract: To study the spatial inhomogeneity of new particle formation (NPF) in the polluted atmosphere of China, we conducted simultaneous measurements at an urban site near a petrochemical industrial area and a regional background site in the Yangtze River Delta region from September to November 2015. At the urban site we observed a type of local NPF event (number of events: n = 5), in which nucleation was limited to a small area but persisted for 6.8 h on average during the daytime. Formation rates of 5 nm particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 68 publications
(78 reference statements)
6
40
2
Order By: Relevance
“…By acting as a sink for LVOC vapors and small clusters, a higher pre-existing aerosol loading is expected to hinder the occurrence of NPF. Existing observations confirm this expectation, since at most measurement sites the average value of CS was found to be lower on NPF event days compared with nonevent days ( Dai et al 2017). An exception to this pattern was the study by Birmili and Wiedensohler (2000) made in Melpitz, Germany, where the average preexisting particle surface areas was somewhat higher on NPF event days compared with all the other days.…”
Section: Formation and Grs Of Charged Particlesmentioning
confidence: 68%
“…By acting as a sink for LVOC vapors and small clusters, a higher pre-existing aerosol loading is expected to hinder the occurrence of NPF. Existing observations confirm this expectation, since at most measurement sites the average value of CS was found to be lower on NPF event days compared with nonevent days ( Dai et al 2017). An exception to this pattern was the study by Birmili and Wiedensohler (2000) made in Melpitz, Germany, where the average preexisting particle surface areas was somewhat higher on NPF event days compared with all the other days.…”
Section: Formation and Grs Of Charged Particlesmentioning
confidence: 68%
“…This implies that regional NPF intensities are likely substantially underestimated if measurements are solely available from urban sites. Dai et al () also found a type of strong local nucleation event at the urban site where the formation rate of particles (e.g., J5) was positively correlated with H 2 SO 4 and enhanced by anthropogenic volatile organic compounds from nearby industrial emissions. This finding highlights that local NPF events might be an important contributor to CCN in polluted urban environments.…”
Section: Aerosol Formation Nucleation Optical Properties and Radiamentioning
confidence: 95%
“…However, NPF and particle growth in highly polluted environments remains less understood . Dai et al (2017) made nearly two months of simultaneous measurements of particle number size and Guo, Gao, et al (2014) WRF with two-moment bulk-bin cloud microphysics and aerosol radiative effect distributions (4-750 nm) at an urban site and a regional background site in the polluted YRD region. They found that the formation and growth rates at the polluted urban site were always lower than those at the regional background site during seven regional NPF events.…”
Section: Aerosol Formation and Growthmentioning
confidence: 99%
“…Spatial variations of nucleation and growth in inhomogeneous air masses thus lead to different evolution patterns of the particle size distribution observed at a fixed monitoring location (Kivekäs et al, ). Dai et al () observed that NPF events in Nanjing were sometimes connected to AVOC plumes emitted from nearby industrial areas. In those local NPF events, nucleation was estimated to occur within a distance of ~50 km upwind of the observation site.…”
Section: Npf Observations In Various Environmentsmentioning
confidence: 99%